The Janus-Faced Role of Cell-Mediated Immune Responses in Pancreatic Cancer - Elena Niccolai; Antonio Taddei; Federica Ricci; Maria Novella Ringressi; Amedeo Amedei (European Medical Journal Oncology, 2017)
Pancreatic cancer (PC) still represents an unresolved therapeutic challenge due to the associated poor prognosis and the lack of responsiveness to current treatments. Surgery, followed by adjuvant therapy, is the only potentially curative treatment for PC; however, only 20% of PC patients have a potential resectable disease at diagnosis and the overall 5-year survival rate does not exceed 20%. In this context, better, more effective strategies are needed. Immunotherapy is an interesting approach for cancer treatments, but increasing evidence testifies that the immune system plays contrasting roles in both tumour elimination and tumour progression. In particular, PC is considered relatively immune resistant due to the characteristic fibrosis, the presence of immunosuppressive cells, and the compact extracellular matrix that defines the tumour microenvironment and allows for the growth of cancer cells. Despite this, there is evidence that PC cells are able to induce an anti-tumour immune response that can impact the disease course. More recently, it has become clear that PC activates both the anti-cancer immune response and the immunosuppressive effects of the immune system; therefore, for the immune-therapeutic strategies to be effective, they should involve not only the stimulation of the immune system but also the control of the immunosuppressive milieu. In this review, we discuss the dual role of immune cells in the onset and progression of PC.